2022
DOI: 10.3390/polym14153209
|View full text |Cite
|
Sign up to set email alerts
|

Fresh, Mechanical, and Durability Behavior of Fly Ash-Based Self Compacted Geopolymer Concrete: Effect of Slag Content and Various Curing Conditions

Abstract: This investigation evaluates the influence of various curing conditions and slag inclusion on the fresh, mechanical, and durability properties of self-compacting geopolymer concrete (SCGC) based on fly ash (FA). Curing temperature and curing time have a vital role in the strength and microstructure of geopolymer concrete. Therefore, to begin the research, the impacts of different curing conditions (curing temperature and curing time) and slag content on the compressive strength of FA-based SCGC were examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…The substitution of slag with FA thus improves the initial setting time of geopolymer paste [18]. It was reported that the inclusion of slag leads to the reduction of the fresh state properties of SCGC, whilst improving the hardened state properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of slag with FA thus improves the initial setting time of geopolymer paste [18]. It was reported that the inclusion of slag leads to the reduction of the fresh state properties of SCGC, whilst improving the hardened state properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…The GP cube samples were then examined for any concrete damage. The materials were weighed and their compressive strength was estimated [10,14,15].…”
Section: Salt Water Exposurementioning
confidence: 99%
“…Experiments are undertaken to establish the durability level of concrete under different types of strength, which are dependent on the proportion of OPC in GPC. The sample trial was separated into two groups, one with GPC cured at room temperature and the other with GPC cured at 60°C for 24 hours [10,15,20]. Figure 1 shows the weight difference between the concrete before and after hydration.…”
Section: Durability Of Gpcmentioning
confidence: 99%
“…In addition, the energy consumption for the production of geopolymer concrete is greatly decreased. For example, compared with ordinary Portland cement concrete with the same strength, the energy consumption of fly ash-based geopolymer concrete is reduced by 70% [ 17 ]. The comparison of energy consumption and CO 2 emissions of ordinary Portland cement and geopolymer is shown in Figure 1 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%